(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The objective of this study is to ascertain whether or not the use of metacognitive strategies during online courses might lead to an improvement in the critical thinking skills of students. The research was conducted utilizing a quasi-experimental, pre- and post-test approach, and it included the participation of one hundred fifty children who were enrolled in educational programs in Balrampur, Uttar Pradesh, India. The Metadig tool was used by one group of participants in order to execute metacognitive strategies, while the other group focused only on the utilization of conventional online learning methods. Participants were assigned to one of the two groups by a random process. For the purpose of evaluating critical thinking skills, which include both substantive and dialogical features, the Critical Thinking Questionnaire was used. For the purpose of data analysis, generalized linear models were used, with pre-test scores being accounted for and Bonferroni coefficients being utilized to compensate for multiple comparisons. According to the findings, Metadig users made considerable development on both of the metrics, with the dialogical component demonstrating the greatest amount of improvement. According to the findings, the incorporation of metacognitive practices into online learning has the potential to significantly enhance the students’ capacities for critical thinking, self-regulation, and reasoning.